Influence of the morphological characteristics and motor abilities at the performance of the left and right katagurume technique in Bosnia and Herzegovina judokas - Mekic, A.; Kajmovic, H.; Rado, I. (Homosporticus, 2009)
Main goal of this research is to determine the influence of the morphological characteristics and motor abilities at the performance of the left and right kata gurume in Bosnia and Hezegovina judokas. Research was conducted in 2008 under the auspices of the Judo association of B&H, during summer training camps in Neum and Trebinje. Sample consisted of 87 judokas, senior and junior age and included all of the seven weight categories. The determination of the morphological characteristics and motor abilities influence at the performance of the kata gurume was done by the use of the regression analysis. Results bring us to the conclusion that the situational efficiency in not only under the influence of the morphological characteristics, body weight precisely but is influenced also by the explosive strength. To conclude, regression analysis paints us a real existing picture which shows that the fundamental ability for the successful and efficient performance of left and right kata -gurume is explosive strength.